Oh là là! Ou le monde reconstruit par les petits mots sans importance - Świątkowska, Marcela (Neophilologica, 2005)
Marcela Świątkowska analyzed the category of interjections in order to present the extent to which these expressions are used for describing the world and to show their role in the construction of characters. In other words, she tried to describe two linguistic ways of constructing the world, both of which employ interjections. The first of them pivots on the use of onomatopoeia, the second one - on the use of stereotypical expressions like Oh là là!, Olé!, Wow! Onomatopoeic expressions imitate the world thus reconstructing the extra-linguistic reality. Such expressions are also used for the description of characters as thanks to the appropriate use of interjections interpreters of the description are able to situate a character in certain social and cultural milieus.